Modern Labor Market: Trends and Features of Development - TUREKULOVA, Dametken; MUKHAMBETOVA, Lyazzat; ISKAKOVA, Gulnar; BERMUKHAMEDOVA, Galiya; BODAUKHAN, Gulbagda (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The article considers the stages of formation and development of the labor market in the Republic of Kazakhstan. Also analyzed the features of functioning of the modern labor market. In the article determined factors of external and internal influence. Had established that the new labor market tendencies have a predominantly negative impact on the state of the Kazakh labor market, its segmentation and structure. In the article had proposed for improving the republican and regional labor markets with the strengthening of the regulatory role of the state.